Pengajaran Membaca Al-Quran pada Etnik Melayu di desa Teluk Batang Kabupaten Kayong Utara - Nazril Hijar; Sukino; Abdul Mukti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
In the Malay community of Teluk Batang Village, North Kayong Regency (KKU), only a few parents enroll their children in Quranic schools (TPA) or hire Quranic tutors to teach at home. The majority, however, opt to send their children to a local